Faktor - Faktor Yang Mempengaruhi Produktivitas Tenaga Kerja Panen Kelapa Sawit (Elaeis Guineensis Jacq.) Di Kebun Bukit Lawang Divisi II PT. Langkat Nusantara Kepong - Walmadri Walmadri; Muhammad Alwy Fadhillah; Febriana Roosmawati; Fastabiqul Khairad (CULTIVATE: Journal of Agriculture Science, 2024)
Oil palm plantations cannot be separated from harvest workers, where harvest labor has an impact on the yield or quality of the fruit which will later be sold to the public. Of course, special attention needs to be paid to the harvest workforce, such as facilities and infrastructure that support good quality of palm oil products. This research was conducted at PT. Langkat Nusantara Kepong, Kebun Bukit Lawang Division II. This research was carried out in July – August 2022. The method used was quantitative descriptive and assisted by using the SPSS application. There are 5 variables taken, namely X1 (Age), X2 (Education Level), X3 (Work Experience), X4 (Salary), X5 (Support Facilities). The results of this research show that the F test together with the independent variables has a significant effect on the productivity of oil palm harvest workers, while the results of the T test on X4 (Salary) and X5 (Support Facilities) have a significant effect on the productivity of coconut harvest workers. palm oil in Bukit Lawang Plantation Division II, PT. Langkat Archipelago Kepong.